Photocatalytic removal of textile wastewater-originated methylene blue and malachite green dyes using spent black tea extract-coated silver nanoparticles - Sikander Ali; Huma Ijaz; Muhammad Usman Ahmad; Rukhma; Najeeb Ullah; Abid Sarwar; Muhammad Jalal Khan; Tariq Aziz; Ashwag shami; Fahad Al-Asmari (Scientific Reports)
Abstract The spent black tea extract was utilized in order to synthesize the spent black tea silver nanoparticles (SBT-AgNPs). Various parameters were tested to yield the best production of SBT-AgNPs. The characterization was conducted by X-Ray diffraction, Scanning electron microscopy, Zeta potential and energy dispersive X-ray (EDX). The XRD analysis showed hkl planes corresponding to (111), (200), (220), (311) planes at 2θ theta deg 38.3°, 40.8°, 64.5°, and 74.2°. The scanning electron microscopy reported the plate like round shaped morphology of the AgNPs. The zeta potential was examined to be -17.5 mV and a size distribution by intensity of 157.6 d. nm was observed. The EDX was employed to determine the purity of samples by reporting a strong peak of silver (Ag). The degradation activity was examined by photocatalytic removal of methylene blue and malachite green dyes from textile wastewater. The textile wastewater showed a decrease of methylene blue by 25% and 58.3%. The malachite green was also reduced by 33.3% and 60%, which was remarkably significant owing to the presence of the complex factor in the natural environment. The study sets a promising record to harbor the full potential of available food waste resource, such as spent black tea to form SBT-AgNPs and its application in the dye removal from textile waste. The multifaceted outcomes of this study resulted in an eco-friendly procedure, thereby reusing the waste material for environmental cleanup.